The Bahá'í faith and African American history: creating racial and religious diversity - Bramson, Loni (Lexington Books, 2019)
The Bahá'í "pupil of the eye" metaphor : promoting ideal race relations in Jim Crow America / Christopher Buck -- "The most vital and challenging issue" : the Bahá'í faith's efforts to improve race relations, 1922 to 1936 / Loni Bramson -- Alain Locke on race, religion, and the Bahá'í faith / Christopher Buck -- The most challenging issue revisited : African American Bahá'í women and the advancement of race and gender equality, 1899-1943 / Gwendolyn Etter-Lewis -- Hand in hand : race, identity, and community development among South Carolina's Bahá'í, 1973-1979 / Louis Venters -- Race unity efforts among American Bahá'í : institutionalized tools and empirical evidence / Mike McMullen -- Race, place, and clusters : current vision and possible strategies / June Manning Thomas.